'ARIGATOU' PHRASE IN JAPANESE DAILY LIFE - Dewi Kania Izmayanti; Zuraidah Sri Handayani Gultom; Dibya Prayassita Somya Rosa (WIDAI Japanese Journal, 2021)
In daily social life, humans cannot be separated with interaction with nature, and it includes giving and receiving. In Japanese society, a gift is always depicted as On or debt which must be repaid in later time. One way to pay On  is through the phrase arigatou.  This research objective is to describe Arigatou phrase based on the meaning and forms of expression inside Japanese society daily life. Methods used in this research is Descriptive Methods which utilizes symbolic interaction theory to analyze the data. Result found is that arigatou was originally addressed to God and gradually used in daily life. From meaning perspective arigatou described as gratitude and social harmony keeper and was addressed to the Emperor as expression of loyalty towards the country with full consent on abiding the law. Meanwhile the phrase arigatou in family is meant to express obedience towards every decision made by the family to maintain honor within said family. Arigatou phrase towards nature is to include them in every element of life. Found conclusion is that Arigatou phrase included Up-Down essence, which means the relation between Kami (God) (Up) and Humans (Down), described arigatou in both form of phrase and meaning.